2014
DOI: 10.3945/jn.114.193771
|View full text |Cite
|
Sign up to set email alerts
|

A Dietary Biomarker Approach Captures Compliance and Cardiometabolic Effects of a Healthy Nordic Diet in Individuals with Metabolic Syndrome

Abstract: Assessment of compliance with dietary interventions is necessary to understand the observed magnitude of the health effects of the diet per se. To avoid reporting bias, different dietary biomarkers (DBs) could be used instead of self-reported data. However, few studies investigated a combination of DBs to assess compliance and its influence on cardiometabolic risk factors. The objectives of this study were to use a combination of DBs to assess compliance and to investigate how a healthy Nordic diet (ND) influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 38 publications
1
39
0
3
Order By: Relevance
“…apples), vegetables, root vegetables and legumes . Controlled trials conducted in various Nordic populations have shown that healthy Nordic diets cause reduction in several key cardiovascular disease (CVD) risk factors . Overall, the reductions in risk factors were of similar magnitude as those previously reported for, for example, Mediterranean and dietary approach to stop hypertension (DASH) diets .…”
supporting
confidence: 58%
“…apples), vegetables, root vegetables and legumes . Controlled trials conducted in various Nordic populations have shown that healthy Nordic diets cause reduction in several key cardiovascular disease (CVD) risk factors . Overall, the reductions in risk factors were of similar magnitude as those previously reported for, for example, Mediterranean and dietary approach to stop hypertension (DASH) diets .…”
supporting
confidence: 58%
“…For example, when butter and other dairy products are iso-calorically replaced with vegetable fats, there is a reduction of 15 : 0 and 17 : 0 in circulating lipids [2529]. In addition, in mixed diets, which either increase or decrease of dairy fats, such intake variations are reflected by changes in circulating OCFAs [3032]. Although these results support the use of 15 : 0 as dairy fat biomarker, the precise dose–response association between dairy fat intake and circulating 15 : 0 can only be obtained by strictly controlled feeding studies in which the quantity and quality of the dairy products are monitored and known [33].…”
Section: Biomarkers Of Dairy Intake: Intervention Studiesmentioning
confidence: 99%
“…Unfortunately, there are very few valid biomarkers available and putative biomarkers identified are typically concentration biomarkers, i.e. biomarkers where the concentrations are correlated with the intake, but where other determinates also may affect the intake‐biomarker relationship . In most cases, only a small proportion of the variation of these markers is explained by direct intake with other determinants typically being unknown.…”
Section: Introductionmentioning
confidence: 99%